Interview with Miroslav Hroch - Joep Leerssen (Studies on National Movements, 2022)
Miroslav Hroch has recently celebrated his 90th birthday. A reason for SNM to ask this pioneer and elder statesman in the comparative study of national movements for a brief interview. The questions and answers were exchanged by e-mail in late 2022/early 2023 in a mixture of English and German.